2015
DOI: 10.1242/jcs.168831
|View full text |Cite
|
Sign up to set email alerts
|

Role of epithelial sodium channels (ENaCs) in endothelial function

Abstract: An increasing number of mechano-sensitive ion channels in endothelial cells have been identified in response to blood flow and hydrostatic pressure. However, how these channels respond to flow under different physiological and pathological conditions remains unknown. Our results show that epithelial Na + channels (ENaCs) colocalize with hemeoxygenase-1 (HO-1) and hemeoxygenase-2 (HO-2) within the caveolae on the apical membrane of endothelial cells and are sensitive to stretch pressure and shear stress. ENaCs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 36 publications
(38 reference statements)
0
48
0
Order By: Relevance
“…For example, ENaC is activated by shear stress in native kidney tubules, endothelial cells, and heterogeneous expression systems (26,41,42). ENaC gating in response to LSS was altered by mutations introduced at key sites within the large ECD and transmembrane helices (43)(44)(45)(46).…”
Section: Discussionmentioning
confidence: 99%
“…For example, ENaC is activated by shear stress in native kidney tubules, endothelial cells, and heterogeneous expression systems (26,41,42). ENaC gating in response to LSS was altered by mutations introduced at key sites within the large ECD and transmembrane helices (43)(44)(45)(46).…”
Section: Discussionmentioning
confidence: 99%
“…LOX‐1‐overexpressing mice fed a high‐fat diet show reduced endothelium‐dependent relaxation as a result of decreased NO availability (Eichhorn et al , ). We have shown that enhanced ENaC activity can also reduce NO production (Liu et al , ; Guo et al , ; Zheng et al , ), suggesting that ENaC can mediate ox‐LDL‐induced endothelial dysfunction. Our data presented here suggest that ox‐LDL stimulates ENaC in endothelial cells by elevating intracellular ROS and this accounts for the decreased aortic relaxation induced by ox‐LDL.…”
Section: Introductionmentioning
confidence: 99%
“…More experiments by using inside-out membrane patches of HEK cells expressing ion channels may further define these two modes and enrich the interplay between iron and CO in ion channels. In the case of heme-dependent CO regulation of ion channels, if heme can be washed out from ion channels such as ENaC 76 , the potential CO effect on channel activity cannot be repeated. However, if heme cannot be washed out from ion channels such as Slo1 BK 57 Ca, the possible CO effect on channel activity may still be repeated once heme is bound.…”
Section: Discussionmentioning
confidence: 99%